Comparative analysis of old, recycled and new PV modules - Haroon Ashfaq; Ikhlaq Hussain; Ajay Giri (Journal of King Saud University: Engineering Sciences, 2017)
This paper presents comparative analysis of old, recycled and new PV modules. It is possible to recycle even very old products by modern standard processes in a value-conserving manner. About 90% of the materials recovered from solar panels can be recycled into useful products. Carbon emission and energy cost are low in manufacturing recycled SPV. Modules can be manufactured with recycled materials and reinstalled in systems as a full quality product with today’s technology good for another 25–30 years. Analysis of all the models of PV module is done with the help of MATLAB. This helps in comparison and proves the effectiveness of the recycled PV module based systems.